2001
DOI: 10.1038/sj.bjp.0703878
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of vasopressin V1A receptor mRNA and protein in vascular smooth muscle cells following cyclosporin A treatment

Abstract: 1 The major side eects of the immunosuppressive drug cyclosporin A (CsA) are hypertension and nephrotoxicity. It is likely that both are caused by local vasoconstriction. 2 We have shown previously that 20 h treatment of rat vascular smooth muscle cells (VSMC) with therapeutically relevant CsA concentrations increased the cellular response to [Arg 8 ]vasopressin (AVP) by increasing about 2 fold the number of vasopressin receptors.3 Displacement experiments using a speci®c antagonist of the vasopressin V 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
1
27
1
Order By: Relevance
“…In addition, we have shown that the effect of CsA on receptor protein expression was preceded by an increase in V 1A receptor mRNA levels starting at 2 h and peaking at 6 -10 h after CsA addition (13). These data suggest that shorter times of CsA exposure may be sufficient to induce V 1A receptor up-regulation.…”
Section: Csa and Analoguesmentioning
confidence: 58%
See 4 more Smart Citations
“…In addition, we have shown that the effect of CsA on receptor protein expression was preceded by an increase in V 1A receptor mRNA levels starting at 2 h and peaking at 6 -10 h after CsA addition (13). These data suggest that shorter times of CsA exposure may be sufficient to induce V 1A receptor up-regulation.…”
Section: Csa and Analoguesmentioning
confidence: 58%
“…At least for vasopressin and angiotensin II, the expression of their respective cell surface receptors was shown to be increased by CsA in rat and human aortic smooth muscle cells (10 -12). Recently, we have shown that CsA up-regulated the vasopressin type 1A (V 1A ) receptor via an increase in the corresponding mRNA levels in RASMC (13). Up-regulation of vasoconstrictor hormone receptors may be responsible for the enhanced vasoconstriction under in vivo conditions, thus leading, via an increase in peripheral resistance, to hypertension and to a decrease in glomerular filtration (4 -6).…”
mentioning
confidence: 99%
See 3 more Smart Citations